Influence of Injection Strategy on B20MOME Fueled CRDI Engine with Toroid Shaped Piston Cavity. Issue 3 (2019) - Kumar, Prashanth; Banapurmath, Nagaraj R; Fernandes, Peter; K, Raju
No abstract available